Modeling Agent-Oriented Methodologies for Landslide Management - Sugiarto, Very; Ramdani, Fatwa; Bachtiar, Fitra (Faculty of Computer Science (FILKOM) Brawijaya University, 2019)
One of the most fatal natural disasters in Batu City was a landslide. The percentage of casualties if directly affected by landslides is 47%. This number is quite large when compared to other natural disasters. Even though the potential of the tsunami is the biggest, when compared to the intensity of the occurrence, landslides are the most common and most often cause fatalities. One of the causes of many fatalities in natural disasters is the lack of preparedness management. For that reason the need to develop a technology that can support to reduce fatalities in landslides is needed. One of the technologies used to prevent the number of fatalities caused by natural disasters is to use multi-agent system. One of the advantages of an agent is use Belief-Desire-Intention (BDI) models for building the Muiti-Agent Systems (MAS). The specific objective of this study was to model a simulated natural disaster landslide using the Prometheus Methodology. Evaluation is done by generating a model using jackCode and implementing it using the Java Agent Development Framework. The results of this study indicate that a model made using the Prometheus Methodology can be used as a simulation of natural disaster preparedness for landslides.